Pemberdayaan Masyarakat Lokal melalui Pelatihan Pemandu Ekowisata di Pulau Binongko, Kabupaten Wakatobi - Sari, Wiwik Nirmala (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This training is part of the Wakatobi District Tourism Office's program on Institutional Development and Human Resources in Tourism and Creative Economy, conducted in May 2023 on Binongko Island, Wakatobi. The aim is to improve the skills of local tourism guides, specifically in ecotourism, on Binongko Island. The training lasted five days with two instructors from academia and industry. Participants included forty individuals from local tourism communities, Pokdarwis, village tourism managers, and local travel agencies. The training process consisted of five stages: preparation and opening, material presentation, field practice, discussion and evaluation, and conclusion. The training progressed smoothly according to the set goals, although areas for improvement were noted. Participants actively engaged with the material, participated in Q&A sessions, and interacted well with the instructors. Practical activities such as guiding and field observation went well, although some participants need to enhance their proficiency in foreign languages, particularly English. During material presentations, participants demonstrated their ability to interpret Binongko's history and culture, yet storytelling skills could be strengthened. Field observations and interviews were conducted effectively, although some participants showed hesitation in interacting with local communities. Overall, the training was successful and is vital to continue for ongoing enhancement of local tourism.